2019
DOI: 10.3390/genes10060409
|View full text |Cite
|
Sign up to set email alerts
|

The Red Fox Y-Chromosome in Comparative Context

Abstract: While the number of mammalian genome assemblies has proliferated, Y-chromosome assemblies have lagged behind. This discrepancy is caused by biological features of the Y-chromosome, such as its high repeat content, that present challenges to assembly with short-read, next-generation sequencing technologies. Partial Y-chromosome assemblies have been developed for the cat (Felis catus), dog (Canis lupus familiaris), and grey wolf (Canis lupus lupus), providing the opportunity to examine the red fox (Vulpes vulpes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
(177 reference statements)
0
6
0
Order By: Relevance
“…The evolutionary dynamics of the Y chromosome involves acquisition, loss, and amplification of genes and genomic regions, resulting in structural complexity and broad variation across mammalian species [ 4 , 10 , 14 , 16 , 18 , 32 , 33 ]. These features complicate MSY sequence assembly and to date, only three primate [ 16 , 33 , 34 ] and the mouse [ 17 ] MSYs are complete, with high-quality MSY draft assemblies available for another handful of mammalian species (gorilla [ 35 ], marmoset [ 19 ], rat [ 19 ], dog [ 32 ], cat [ 32 ], pig [ 16 ], bull [ 19 , 36 , 37 ], horse [ 18 ], and opossum [ 19 ]), and partial MSY sequences have been obtained for a few more domestic and wild species (goat [ 38 ], sheep [ 27 , 29 ], red fox [ 39 ], brown and polar bears [ 40 , 41 ], and whales [ 42 ]).…”
Section: Introductionmentioning
confidence: 99%
“…The evolutionary dynamics of the Y chromosome involves acquisition, loss, and amplification of genes and genomic regions, resulting in structural complexity and broad variation across mammalian species [ 4 , 10 , 14 , 16 , 18 , 32 , 33 ]. These features complicate MSY sequence assembly and to date, only three primate [ 16 , 33 , 34 ] and the mouse [ 17 ] MSYs are complete, with high-quality MSY draft assemblies available for another handful of mammalian species (gorilla [ 35 ], marmoset [ 19 ], rat [ 19 ], dog [ 32 ], cat [ 32 ], pig [ 16 ], bull [ 19 , 36 , 37 ], horse [ 18 ], and opossum [ 19 ]), and partial MSY sequences have been obtained for a few more domestic and wild species (goat [ 38 ], sheep [ 27 , 29 ], red fox [ 39 ], brown and polar bears [ 40 , 41 ], and whales [ 42 ]).…”
Section: Introductionmentioning
confidence: 99%
“…We then sequenced the pooled enriched library on an Illumina MiSeq lane SR300 at the UC Davis Genome Center. Additionally, we included HiSeq2500 reads (PE 150) from 2 male red fox whole-genome shotgun libraries sequenced for a different project [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…2013; Rando et al . 2019); the Chinese raccoon dogs were examined by us for the first time. We further analyzed the copy number of the 5′‐flanking region of the SRY and found that, in each animal, the number of the CDS and 5′‐flanking sequences were concordant.…”
Section: Species/dog Breed Copy Number In Dsd Dogs (N; %) Copy Number In Controls (N; %)mentioning
confidence: 99%
“…The modal number of SRY copies in dogs, wolves, Chinese raccoon dogs, and red foxes was 3, 3, 3, and 1 respectively; however, variability of the copy number was only observed in Yorkshire Terriers and red foxes (Table 1). In earlier studies, the SRY copy number was found to be 7, 3, and 1, in dogs, wolves, and red foxes respectively (Li et al 2013;Rando et al 2019); the Chinese raccoon dogs were examined by us for the first time. We further analyzed the copy number of the 5 0 -flanking region of the SRY and found that, in each animal, the number of the CDS and 5 0 -flanking sequences were concordant.…”
mentioning
confidence: 96%
See 1 more Smart Citation